Plasma membrane coenzyme Q: evidence for a role in autism - Crane FL (Dove Medical Press, 2014)
Frederick L Crane,1 Hans Löw,2 Iris Sun,1 Placido Navas,3 Anna Gvozdjáková41Department of Biological Sciences, Purdue University, West Lafayette, IN, USA; 2Department of Molecular Medicine, Karolinska Institute, Stockholm, Sweden; 3Centro Andaluz de Biología del Desarrollo, Universidad Pablo de Olavide, Sevilla, Spain; 4Pharmacobiochemical Laboratory of Third Medical Department, Medical Faculty, Comenius University in Bratislava, Bratislava, SlovakiaBackground: The Voltage Dependent Anion Channel (VDAC) is involved in control of autism. Treatments, including coenzyme Q, have had some success on autism control.Data sources: Correlation of porin redox activity and expression of autism is based on extensive literature, especially studies of antibodies, identification of cytosolic nicotinamide adenine dinucleotide reduced (NADH) dehydrogenase activity in the VDAC, and evidence for extreme sensitivity of the dehydrogenase to a mercurial. Evidence for a coenzyme Q requirement came from extraction and analog inhibition of NADH ferricyanide reductase in the erythrocyte plasma membrane, done in 1994, and reinterpreted when it was identified in VDAC in 2004. The effects of ubiquinol (the QH2 – reduced form of coenzyme Q) in children with autism were studied.Results: A new role for coenzyme Q in the porin channels has implications on autism. Ubiquinol, the more active form of coenzyme Q, produces favorable response in children with autism. Agents which affected electron transport in porin show parallel effects in autism.Conclusion: We propose a hypothesis that autism is controlled by a coenzyme Q-dependent redox system in the porin channels; this conclusion is based on the effects of agents that positively or negatively affect electron transport and the symptoms of autism. The full understanding of the mechanism of their control needs to be established.Keywords: porin, channel, oxidation, reduction, autism